Extremely young melt infiltration of the sub-continental lithospheric mantle - Turner, S; Turner, M; Bourdon, B; Cooper, K; Porcelli, D (Elsevier, 2019)
It has long been inferred that mantle metasomatism and the incompatible element enrichment of the continents both require movement of melts formed by very low degree melting of the mantle. Yet establishing the presence of these melts and whether this process is on-going and continuous, or spatially and temporally restricted, has proved difficult. Here we report large U-Th-Ra disequilibria in metasomatised, mantle xenoliths erupted in very young lavas from the Newer Volcanics Province in southeastern Australia. The 226Ra-230Th disequilibria appear to require reappraisal of previous estimates for the age of eruption that now seems unlikely to be more than a few kyr at most. We propose that infiltration of carbonatitic melts/fluids, combined with crystallization of pargasite, can account for the first order U-series disequilibria observations. Irrespective of the exact details of the complex processes responsible, the half-lives of the nuclides require that some of the chemical and isotopic disturbance was extremely young (« 8 kyr) and potentially on-going at the time of incorporation into the alkali basalts that transported the xenoliths to the surface. This provides evidence for the presence and possibly continuing migration of small melt fractions (~0.02%) in the upper convecting mantle that may contribute to the seismic low velocity zone. By implication, it appears that the asthenosphere must lie close to its solidus, at least in this region. Pressure-temperature estimates indicate that the small degree melts identified could infiltrate as far as 25 km upwards into the sub-continental lithospheric mantle leading to strong incompatible element enrichment and the recent timing of this event this urges a reappraisal of the meaning of 300–500 Ma Nd model ages in mantle xenoliths from this region. In principle, the resultant metasomatised mantle could provide a component for some ocean island basalts, should the sub-continental lithospheric mantle be returned to the asthenosphere by convective removal at some later time.